A hydrogen-driven biocatalytic approach to recycling synthetic analogues of NAD(P)H. Issue 75 (1st September 2022) - Reeve, Holly A.; Nicholson, Jake; Altaf, Farieha; Lonsdale, Thomas H.; Preissler, Janina; Lauterbach, Lars; Lenz, Oliver; Leimkühler, Silke; Hollmann, Frank; Paul, Caroline E.; Vincent, Kylie A.
Abstract : Soluble hydrogenase enables atom efficient, H2 -driven, recycling of synthetic nicotinamide cofactors. Abstract : We demonstrate a recycling system for synthetic nicotinamide cofactor analogues using a soluble hydrogenase with turnover number of >1000 for reduction of the cofactor analogues by H2 . Coupling this system to an ene reductase, we show quantitative conversion of N -ethylmaleimide to N -ethylsuccinimide. The biocatalyst system retained >50% activity after 7 h.